Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Tindak Kekerasan Berdasarkan Undang-Undang Nomor 35 Tahun 2014 - Rismawati, Jesica; Priyana, Puti (Jurnal Ilmiah Wahana Pendidikan, 2024)
Children are a divine gift given by God to parents to be given sincere love and have their rights fulfilled, this is stated in Law Number 23 of 22 concerning Child Protection in the Republic of Indonesia. It is expressed that kids' freedoms are important for obligatory common liberties. Monitored, Secured, and Satisfied by Guardians, Family, People group, Government, and State. As the years go by, violence often occurs throughout society, both in the lower, middle and even upper classes who have higher education. The existence of this violence does not look at age, status or gender. Violence can occur anytime, anywhere if the perpetrator has lost his common sense, which almost resembles the thinking of primitive people who do not have a sense of humanity. Forms of violence against children include acts of physical violence and non-physical violence. Acts of physical violence are actions aimed at injuring, torturing and abusing other people. Meanwhile, acts of non-physical violence are actions aimed at lowering the victim's image or self-confidence. Ordinary acts of violence threaten the lives of other people, whether adults, teenagers or even minors.